Delphie and the galss slippers - Bussell, Darcey (London harpercollins children's book, 2008)
Prima Ballerina Darcey Bussell takes you on a captivating journey to a faraway land of ballet and magic, the wonderful world of Enchantia! The fourth of sparkly new series for all young girls who dream of being a ballerina, or simply love to dance. King Rat is causing havoc in Enchantia again, by playing around with the Big Clock and making time whizz by. Cinderella finds herself always going to the ball, but never meeting her Prince! Can Delphie help?
English Stories
Keywords: English stories